Audit Tata Kelola Teknologi Informasi Pada PT. EMD Menggunakan COBIT 4.1 dan BSC - Tomas, Jordi; F. Andry, Johanes (Institut Teknologi dan Bisnis Kalbis, 2019)
PT. EMD is a company engaged in the distributor of various kinds of Hardware and Lifestyle products. The company is currently in the stage of implementing an information systemaudit. Previously, this company had implemented an information system as a strategy to support the achievement of business profits in competing in market share. This study aims to assess the information technology governance that has been implemented by the company, so that the writer can provide recommendations for companies to improve the performance of information technology governance. This research uses descriptive research method because it includes data, analysis and interpretation. This research is structured as an inductive research that searches and collects existing data in the field with the aim to measure the level of maturity and recommendation improvement on information technology governance.